Some factors affecting milk yield of Holstein-Friesian dairy cows imported to Ghot-Al Sultan Project (Libya) - Amaizik, Amaizik, S. A; Amir, M. A. (Al-Mukhtar Journal of Sciences, 2015)
This study was carried out to determine the effects of calf sex, insemination system (artificial or natural service) and number of services per conception on milk yield of dairy cows. 160 production records of Holstein-Friesian dairy cows (age 3-5 years) imported to Ghot-Al Sultan Project (Libya) were studied. The milk yield of the first five months of lactation season (during year, 2004) was used. Average monthly milk yield was also included in the study. The results of study showed that, daily milk yield of cows which calved males was significantly (P<0.05) greater than daily yield of those cows calved females (21.0 vs. 19.1 l) with about 290 liters for the whole period of study. The daily milk yield of cows were served naturally increased significantly (P<0.05) than the yield of those cows inseminated artificially (21.65 vs. 20.85 l) with about 124 liters for the whole period of study. Daily milk yield of cows were served one time was significantly (P<0.05) lower when compared with yield of those cows which were served two times (20.25 vs. 21.23 l) with about 148 liters for the whole period of study. Milk yield of cows which were served three times did not differ (P>0.05) with yield of above two groups. It is concluded that, the calf sex, type of insemination and number of services per conception significantly affected milk yield in Holstein-Friesian dairy cows imported and raised under Libya conditions.